A novel photosensitizer: An l-glutamide lipid conjugate with improved properties for photodynamic therapy. Issue 12 (22nd November 2016) - Nathan, Erica; Vijayashree, K.; Harikrishna, A.; Takafuji, Makoto; Jintoku, Hirokuni; Ihara, Hirotaka; Rao, N. M.
Abstract : Liposomes prepared with a lipid conjugated photosensitizer (Lipid-PS) enhances the cellular uptake of the PS and also improves photo-induced cell death compared to the liposomes with free PS. Abstract : Photosensitizers (PS) are used in photodynamic therapy to treat several cancers. The efficacy of photodynamic therapy (PDT) could be further improved by overcoming aggregation-dependent quenching of PS and by improving the biodistribution of the PS. In this work we attempted to overcome these issues by conjugating a PS with a lipid molecule and tested the liposomes prepared with this PS conjugated lipid for PDT. A novel lipid–porphyrin conjugate (1 : 1) was synthesized by attaching a PS, 5-(4-methoxycarbonylphenyl)-10, 15, 20-triphenyl- 21 H, 23 H-porphine, to the head group of a glutamide lipid. Two liposomal preparations, with egg phosphatidylcholine as the bulk lipid, were prepared viz . liposomes with PS conjugated lipid (LPSL) and PS entrapped in liposomes (PSL). At equimolar concentrations of the PS, both liposomal preparations were found to generate comparable amounts of reactive oxygen species as free PS upon light exposure. Electron micrographs and dynamic light scattering measurements indicated uniform and circular liposomes of 150 nm in size and near neutral zeta potential. Uptake of these liposomes by the human ovarian carcinoma cell line, SK-OV-3, was shown by FACS and confocal microscopy. Upon light exposure, the LPSL, i.e., with the conjugate lipid, have shown a substantial decrease (>4 times) in the PS requirement compared to PSL or free PS in its ability to cause light mediated cell death of SK-OV-3 cells. The light mediate cell death by LPSL was shown to be not dependent on the bulk properties of the lipid. Our data suggest a potential benefit of conjugating PS with a lipid in improving the efficiency of PDT.